2019
DOI: 10.1093/jxb/erz497
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Loliolide, the most ubiquitous lactone, is involved in barnyardgrass-induced rice allelopathy

Abstract: Neighbor detection and allelochemical response are important mediators in plant-plant interactions. Despite increasing knowledge of plant allelochemicals in response to the presence of competitors involved in the neighbor-derived signaling chemicals, less is known about which signaling chemicals are responsible for the neighbor-induced allelochemical response. Here, we experimentally demonstrated (-)-loliolide, a carotenoid metabolite, as a signaling chemical in barnyardgrass-rice allelopathic interactions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 57 publications
0
46
0
1
Order By: Relevance
“…(-)-Loliolide, a carotenoid metabolite, is the most ubiquitous monoterpenoid lactone in plant families (Grabarczyk, Wi nska, Mączka, Potaniec, & Anioł, 2015). Recent studies have shown that (-)-loliolide may act as a signalling chemical in plant defences against weeds (Li et al, 2020), pathogens (Pan et al, 2009) and herbivores (Murata et al, 2019). Plants can detect (-)-loliolide released from the roots of interacting plant species and then respond by increased production of allelochemicals to benefit their own growth.…”
Section: Signalling Chemicals and Their Methodological Approachesmentioning
confidence: 99%
“…(-)-Loliolide, a carotenoid metabolite, is the most ubiquitous monoterpenoid lactone in plant families (Grabarczyk, Wi nska, Mączka, Potaniec, & Anioł, 2015). Recent studies have shown that (-)-loliolide may act as a signalling chemical in plant defences against weeds (Li et al, 2020), pathogens (Pan et al, 2009) and herbivores (Murata et al, 2019). Plants can detect (-)-loliolide released from the roots of interacting plant species and then respond by increased production of allelochemicals to benefit their own growth.…”
Section: Signalling Chemicals and Their Methodological Approachesmentioning
confidence: 99%
“…The sessile lifestyle of plants necessitates a great arsenal of metabolites that protect against herbivores and pathogens. This arsenal includes the so‐called plant activators, such as the phytohormone jasmonic acid (JA), which is involved in plant–pathogen protection through the activation of defense mechanisms that do not harm/kill the microbes or insects (Wei et al ., 2011; Caceres et al ., 2016; Murata et al ., 2019a,b; Li et al ., 2020). In addition, plants defend themselves by using metabolites that affect pathogens and exert antimicrobial or insecticidal activity.…”
Section: Cyclic and Acyclic Apocarotenoids With Signaling Propertiesmentioning
confidence: 99%
“…In addition, plants defend themselves by using metabolites that affect pathogens and exert antimicrobial or insecticidal activity. Interestingly, several cyclic apocarotenoids that induce herbivore resistance in plants without exhibiting insecticidal activity have been reported in the last years (Wei et al ., 2011; Caceres et al ., 2016; Murata et al ., 2019a,b; Li et al ., 2020). Examples of such apocarotenoids are α‐ionone, β‐ionone and loliolide, which arise through the degradation of α‐ and β‐carotene (Schwab et al ., 2008).…”
Section: Cyclic and Acyclic Apocarotenoids With Signaling Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found in marine ecosystems in different brown seaweeds, such as Sargassum horneri [35],Sargassum ringgoldianum subsp. coreanum [36], and Undaria pinnatifida [37], revealing antioxidant, anti-fungal, antibacterial and anticancer properties [34][35][36].…”
Section: Introductionmentioning
confidence: 99%